Efficiency of DMSO as hydroxyl radical probe in an Electrochemical Advanced Oxidation Process − Reactive oxygen species monitoring and impact of the current density. (20th August 2017) - Abou Dalle, Arwa; Domergue, Lionel; Fourcade, Florence; Assadi, Aymen Amin; Djelal, Hayet; Lendormi, Thomas; Soutrel, Isabelle; Taha, Samir; Amrane, Abdeltif
Highlights: Highest hydrogen peroxide concentration and MTZ mineralization obtained for 0.07 mA cm −2 . The evolution OH concentration was not in accordance with that of MTZ mineralization. Dissolved oxygen can become a limiting reagent for OH quantification with DMSO. DMSO can be oxidized and reduced at the electrodes surface distorting OH quantification. DMSO efficient as OH probe until 0. 07 mA cm −2 in this study, not efficient for electro-oxidation. Abstract: In electro-Fenton process, current density is a key operating parameter for organic compound mineralization. In order to explain mineralization yields obtained during the electrochemical treatment of an antibiotic metronidazole (MTZ) in a mono-compartment batch reactor, the evolution of the reactive oxygen species was discussed. Dissolved oxygen, Hydrogen peroxide and hydroxyl radical (OH) concentrations were followed during electrolysis performed at current intensities from 50 to 600 mA corresponding to current densities from 0.04 to 0.45 mA cm −2, using a three dimensional graphite felt as working electrode. Dimethylsulfoxide (DMSO) was used to trap hydroxyl radicals by the production of a stable intermediate, methanesulfonate; however the evolution of hydroxyl radical concentration was not in accordance with MTZ mineralization yields. Results showed that on the one hand, for the highest studied current densities, dissolved oxygen could become a limiting reagent for the OH quantification. On the other hand, DMSO can be oxidized and reduced at the electrodes surface. Indeed, Dimethyl sulfide (DMS), a byproduct from the electrochemical reduction of DMSO was detected during the electrolysis. DMSO appeared therefore relevant as a hydroxyl radical probe in the case of the electro-Fenton process only for low applied current densities, until 0.07 mA cm −2 in the present study.